John Brough letter and biographical sketch - Brough, John, 1811-1865.
Letter and biographical sketch.
In part, typewritten transcript.
Journalist and newspaperman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Journalists; Newspapermen